Shielded Aircraft Windows to Protect Radio Altimeters in the Presence of Wireless Avionics Intra-Communication - Konter, Y.E.J.; Blaauw, K.; Lansink Rotgerink, J.H.G.J. (IEEE, 2023)
Wireless Avionics Intra-Communications in the frequency range of 4.2 to 4.4 GHz is an upcoming solution to replace the cabling of part of the data network in aircraft with a wireless alternative. This solution shares its frequency band with the radio altimeter and is therefore subject to limitations on the transmitted power to ensure compatibility with flight critical equipment of the aircraft. This paper presents simulation results on the effectiveness of shielded aircraft windows to protect radio altimeters in the presence of wireless avionics intra-communication. A propagation model is developed to simulate how shielded cabin windows affect the EIRP of WAIC transmitters within the cabin of an aircraft. Simulation with this model show that a reduction in EIRP of roughly 15 dB can be expected when electromagnetic coating is applied to the passenger windows. These results can be used in the design of robust WAIC network solutions that are compatible with legacy aircraft equipment.